Signalling, work experience and MBA starting salaries - Bhattacherjee, Debashish; Karve, Amol; Krishna, Karthik (2001)
This paper investigates the determinants of MBA starting salaries using a unique placement database from one of the `premier' business schools in India. We invoke some simple arguments regarding schooling, human capital theory and signalling from the economics of human resources to theoretically inform our analysis. The results indicate that there are large salary returns to academic performance and mild returns to prior work experience when the entire sample is studied. However, when the functions are run separately for the domestic and international sector, we find that only academic performance is significant in the domestic sector whereas only prior work experience is significant in the international sector. We interpret the latter result as approximating a `perfectly separating signalling equilibrium' process. - Reproduced
Keywords: Management education; Management